CHANGES IN TIME SENSE IN EXTREME STUNTS - Emil Videv (Scientific Publishing House. NSA Press, 2023)
For the purpose of this research, experienced stuntmen were given the task of performing an extreme action - a jump from a height of 11 meters. Some psycho-physiological and biochemical reactions were studied, giving indications of the changes in the activity of the sympathetic nervous system of the subjects in such an extreme situation. One of the tasks of the study was to determine how such a stressor affects their sense of time. In the publication, we present the conclusions drawn on the basis of the obtained results. The research included work in normal and extreme situations. In the first case, it took place in a hall, while in the second one, it took place on the edge of an 11 meters platform. The experiment was conducted in two variants. In the first, the subjects were required to count the time between two sound signals issued by a computer, and in the second variant - to jump off the edge of the platform at a randomly determined by the computer second after the first signal. In the hall, they jumped from a height of 20cm and in the extreme situation - from 11m. The results were subjected to a mathematical-statistical processing with SPSS 20. Some of our findings overlapped with findings made by other researchers, but some were diametrically opposed. We noticed that in an extreme situation, the subjectively calculated time of the person changes its course. For those motivated to act, it slowed down its course, and for those motivated to give up, it accelerated.